Breast self-exam: do women know about it? - Samia Melissa Bezerra Nogueira; Maria Albertina Rocha Diógenes; Ângela Regina de Vasconcelos Silva (Rev Rene)
The aim of this research is to evaluate women’s knowledge about Breast Self-Exam (BSE) in a private institution. It was an exploratory descriptive study, conducted in August and September, 2003. The sample was composed of 31 women. The data was obtained through semi-structured interview. The analysis showed that 21 (67,7%) women affirm that the BSE prevents nodules from appearing in the breast, eight (25,8%) do not know its purpose and two (6,5%) claimed to know the real meaning of BSE. With regard to the technique to do the BSE, nine (54%) of the interviewees do it by only palpating the breast; six (30%), besides palpating the breasts, do the nipples expression; three (15%) palpate the breasts, the armpit region and do the nipples expression, and only one (5%) practices the technique correctly. It was verified that the women do not know the meaning of the BSE, even if they have been oriented towards its importance, being difficult to make the precocious diagnosis of breast cancer.